5d-3.3=7.5

Simple and best practice solution for 5d-3.3=7.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5d-3.3=7.5 equation:


Simplifying
5d + -3.3 = 7.5

Reorder the terms:
-3.3 + 5d = 7.5

Solving
-3.3 + 5d = 7.5

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '3.3' to each side of the equation.
-3.3 + 3.3 + 5d = 7.5 + 3.3

Combine like terms: -3.3 + 3.3 = 0.0
0.0 + 5d = 7.5 + 3.3
5d = 7.5 + 3.3

Combine like terms: 7.5 + 3.3 = 10.8
5d = 10.8

Divide each side by '5'.
d = 2.16

Simplifying
d = 2.16

See similar equations:

| 17x-8x-9=76-40 | | n=15+2m-4 | | 5(3c-c)+3=43 | | (3x+2)(x+1)=4 | | 2w+9w+2w+8w+7w+w= | | 4a-2=7a-6 | | 6f+30=2f-8 | | 4(x+7.50)=40 | | 118-(3xb)= | | 4x-8=x+25 | | 49-2x=7x+16 | | 11-10x=103-38x | | 139-3x=6x+22 | | 2x+3(x-1)=27 | | 3(1+Y)=3-(5y+2) | | -17=-5+4u | | 2-6x=10-8x | | 4j-1+7= | | 15y=14(y+16) | | 3g+3(-5+4g)=1-g | | 2x^2-7x-16=-3x | | 3x+10=45-2x | | 3(6x-4)=22x | | 3(n-1)-2=4(n-4)-(n-11) | | 2(8q-1)+3(5q+6)= | | 12=2w+2 | | 10(x-5)=9(x+5) | | 9a-4+3a-33=23 | | 2(x-3)+4x=18 | | 5y-5=-35 | | 2(x-3)+4x=6.5 | | 7x-3x-8=24 |

Equations solver categories